Determinan kepatuhan pajak UMKM di Kota Batu pada era PP 23/2018 - Agustinus Cendra Manto; Norman Duma Sitinjak (University of Merdeka Malang, 2024)
The tax collection system in Indonesia is a self-assessment system. A system that relies on taxpayer compliance. This research examines MSME taxpayer compliance. The population chosen was MSMEs in Batu City, East Java. Batu city is a tourist destination. The analysis technique used is multiple regression. The results of the research are that understanding and awareness of taxpayers has an impact on tax compliance, where understanding taxes has the biggest impact. MSMEs in Batu City always prepare funds to pay taxes and understand the benefits of taxes. Tax sanctions are not a consideration for Batu City SMEs because they pay on time.